Beyond Neutrality: Indian Theology and Social Theory - Beltramini, Enrico (Theology today, 2026)
This article argues that any use of social theory by Indian theologians is inherently non-neutral, challenging the widespread assumption that theology can rely on an unbiased social theory for analyzing society. When theologians adopt neutral social theory, they inadvertently import Western intellectual paradigms rooted in modernity, Enlightenment rationality, Christian theology, and Eurocentrism. On the other hand, attempts to resist Western influence by using local or contextual frameworks often lead to mistakenly consider the nation as distinct from the state and the state as a neutral arena. The article presents a theological response to this dilemma, arguing that theologians must abandon the pursuit of neutrality and instead adopt a posture of reflexive engagement.